TOPOLOGY OPTIMIZATION OF PACKAGE SEALER JAW CHASSIS OF AUTOMATIC PACKAGING MACHINE: Received: 07th October 2022; Revised: 18th November 2022, 23rd November 2022, 25th November 2022; Accepted: 28th November 2022 - Erez, Arif Sercan; Filik, Alim; Temizel, Volkan (MATTER: International Journal of Science and Technology, 2023)
After the Covid-19 epidemic, the need to reach hygienic and sealed packaged food products has gained importance and the packaging machinery sector has become an important sector. In this context, the need for special packaging machines has increased. The jaw mechanism of the packaging machine developed within the scope of the study performs the package closing function by opening and closing 200 times per minute, and the jaw chassis carrying the jaw mechanism is exposed to the same series of movements. The design of the jaw chassis should be as light as possible so that no additional load is placed on the motors that provide the movement, while its strength should be high since it carries the entire load from the jaw plates to the motors. To solve this problem, a structural optimization solution called topology optimization, which regulates the distribution of the elements in the design volume within the framework of the determined constraints, is used. With the performed topology optimization study, it has been determined that the new solid model, which continues to provide sufficient strength when exposed to 5000 N force, provides 11% weight gain. This work has been a pioneer for new research to obtain lightweight designs.